2016
DOI: 10.1111/acer.13267
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric, Demographic, and Brain Morphological Predictors of Relapse After Treatment for an Alcohol Use Disorder

Abstract: Background Relapse in alcohol use disorders (AUD) is related to a complex interplay among multiple biological, psychiatric, psychological and psychosocial factors, which may change dynamically during and after treatment. At treatment entry for AUD, morphological abnormalities in anterior frontal regions and the insula have been observed in those who ultimately relapse following treatment. The goal of this study was to determine if measures anterior frontal and insula measures of regional brain thickness, surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 60 publications
5
54
0
4
Order By: Relevance
“…The structural integrity of components of circuits subserving fundamental aspects of executive functions, assignment of external and internal stimulus salience, and emotional/ mood regulation (Seeley et al, 2007;Volkow & Baler, 2014;Williams, 2016), as assessed by volumetric voxel-wise and ROI analyses, has been repeatedly shown to relate to treatment outcome [see (Durazzo & Meyerhoff, 2017;D. Seo & Sinha, 2015) and references therein].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural integrity of components of circuits subserving fundamental aspects of executive functions, assignment of external and internal stimulus salience, and emotional/ mood regulation (Seeley et al, 2007;Volkow & Baler, 2014;Williams, 2016), as assessed by volumetric voxel-wise and ROI analyses, has been repeatedly shown to relate to treatment outcome [see (Durazzo & Meyerhoff, 2017;D. Seo & Sinha, 2015) and references therein].…”
Section: Discussionmentioning
confidence: 99%
“…Seo & Sinha, 2015) and references therein]. Correspondingly, dysfunction in executive skills, impulse control, and assignment of stimulus salience and mood disorders are associated with relapse in AUD (Bates, Buckman, & Nguyen, 2013;Durazzo & Meyerhoff, 2017;D. Seo & Sinha, 2014;S.…”
Section: Discussionmentioning
confidence: 99%
“…Although there may be concerns about providing smoking treatment concurrent with alcohol treatment, most studies find that concurrent smoking and alcohol treatment do not yield worse outcomes than treating alcohol alone (for recent reviews, see McKelvey et al, 2017; Thurgood et al, 2016). As cigarette use increases craving to use alcohol (Cooney et al, 2007; Dermody and Hendershot, 2017; Verplaetse and McKee, 2017), is related to decreased cognitive recovery in adults with AUDs (Durazzo et al, 2006, 2014; Pennington et al, 2013), and is associated with poorer AUD outcomes (Durazzo and Meyerhoff, 2017; Weinberger et al, 2015), combined smoking and alcohol treatment may offer significant benefits for alcohol treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses of structural imaging data from a similar cohort (Durazzo et al, 2017, Durazzo et al, 2015) revealed that ALC had significant increases in gray matter (GM) volumes in the frontal, parietal and occipital lobes between 1 week and 7.5 months of abstinence; the monthly GM volume change rates in the entire frontal and parietal lobes were significantly greater between 1 week and 1 month of abstinence than between 1 month and 7.5 months of abstinence, suggesting a non-linear trajectory of GM volume recovery in these lobes. Clinically relevant modulators of the degree of regional volume reduction in adult ALC and of the extent of volume recovery during abstinence have been identified, such as age, gender, genetic factors, family history of problem drinking, concurrent chronic cigarette smoking, and comorbid medical, psychiatric, and substance use disorders (Cardenas et al, 2005, Demirakca et al, 2011, Durazzo et al, 2007a, Durazzo et al, 2007b, Durazzo and Meyerhoff, 2017, Gazdzinski et al, 2005b, Hoefer et al, 2014, Mon et al, 2013, Pennington et al, 2015). However, it is unclear if the volume reductions and longitudinal change trajectories also exist in functionally distinct sub-regions within the lobar GM regions that are critically important to addictive behavior.…”
Section: Introductionmentioning
confidence: 99%